2021
DOI: 10.1002/lno.11700
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of external nutrient loading and internal cycling to cyanobacterial bloom dynamics in Lake Taihu, China: Implications for nutrient management

Abstract: Harmful cyanobacterial blooms (CyanoHABs) are linked to increasing anthropogenic nitrogen (N) and phosphorus (P) inputs. However, CyanoHABs in many large lakes continue despite extensive abatement efforts, mostly focused on external P loading. Internal nutrient cycling can modify nutrient availability and limitation; thus, understanding the relative importance of external vs. internal nutrient loading is essential for developing effective mitigation strategies for CyanoHABs. We estimated long‐term nutrient bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(48 citation statements)
references
References 99 publications
1
47
0
Order By: Relevance
“…In shallow eutrophic lakes, in-lake TN:TP ratios are often low in summer due to the high denitrification and strong P release at high temperatures (Xu et al, 2010;Xu et al, 2021;Søndergaard et al, 2013;Søndergaard et al, 2017;Shatwell and Köhler, 2019). From a resource availability perspective, excess N loading could directly increase the summer phytoplankton biomass via alleviation of temporal N deficiency, and this has been confirmed by numerous bioassays and mesocosm experiments (Xu et al, 2010;He et al, 2015;Kolzau et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In shallow eutrophic lakes, in-lake TN:TP ratios are often low in summer due to the high denitrification and strong P release at high temperatures (Xu et al, 2010;Xu et al, 2021;Søndergaard et al, 2013;Søndergaard et al, 2017;Shatwell and Köhler, 2019). From a resource availability perspective, excess N loading could directly increase the summer phytoplankton biomass via alleviation of temporal N deficiency, and this has been confirmed by numerous bioassays and mesocosm experiments (Xu et al, 2010;He et al, 2015;Kolzau et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…blooms (Guo et al, 2007;Qin et al, 2019). Previous bioassay experiments and field monitoring studies have revealed that the phytoplankton in Lake Taihu is generally N limited or N, P co-limited during summer and fall (Xu et al, 2010;Xu et al, 2021;Paerl et al, 2011). Thus, our hypothesis was that with increasing N loading in summer, the phytoplankton biomass would increase due to the alleviation of N deficiency and higher sediment P release.…”
Section: Introductionmentioning
confidence: 99%
“…The regeneration of ammonium through active ammonium recycling is likely to supports high phytoplankton production during the springsummer season in the YRE. Previous studies have suggested that water column N recycling contributes significantly to phytoplankton N demand in aquatic environments (Bronk et al, 2014;Hampel et al, 2018;Jiang et al, 2019;Xue et al, 2021a;Xue et al, 2021b;Xu et al, 2021;Hoffman et al, 2022). In the West Florida Shelf, regenerated ammonium was sufficient to supply the ammonium demand, and supported 85% of the ammonium uptake even during blooms of Karenia brevis (Bronk et al, 2014).…”
Section: Implications Of Estuarine Dam On Ammonium Recyclingmentioning
confidence: 93%
“…In world’s large bloom-impacted lakes, such as Lake Taihu (China) and Lake Champlain (Canada/USA), , nitrogen (N) concentration often tended to be scarce with the development of cyanobacterial blooms, presumably a result of the high rate of denitrification . Consequently, cyanobacterial aggregates generally experienced strict N limitation when the blooms reached their peak biomass. , The intensity of N limitation is expected to be stronger because of the imbalanced nutrient reduction efforts/efficiencies, for example, along with the substantial and constant reductions of N concentration and nutrient stoichiometry (i.e., TN:TP ratios) in Lake Taihu during the past decade. , Nitrogen can play an important role in the regulation of EPS production in cyanobacteria. Specifically, N limitation can often elevate EPS production, alter EPS structure and composition, and then shape the morphology and colony size of cyanobacterial aggregates . The imbalanced nutrient reduction is thus likely to promote the cyanobacterial capacity for P storage in their EPS and then increase the total cyanobacterial particulate P quota (including both P stored in EPS and cells).…”
Section: Introductionmentioning
confidence: 99%